A water-soluble pillar[5]arene as a new carrier for an old drug. Issue 15 (31st March 2017) - Barbera, Lucia; Franco, Domenico; De Plano, Laura M.; Gattuso, Giuseppe; Guglielmino, Salvatore P. P.; Lentini, Germana; Manganaro, Nadia; Marino, Nino; Pappalardo, Sebastiano; Parisi, Melchiorre F.; Puntoriero, Fausto; Pisagatti, Ilenia; et al.
Abstract : The ability of deca-carboxylatopillar[5]areneWP5 to bind the antibiotic amikacin and modulate its antimicrobial response towards Gram-positive bacteria is reported. Abstract : The remarkable affinity of deca-carboxylatopillar[5]areneWP5 towards the aminoglycoside antibiotic, amikacin, in aqueous media is reported; in vitro studies on Gram-positive bacteria ( Staphylococcus aureus ) show that drug entrapment insideWP5 also takes place in the presence of the microrganisms, thus pointing toWP5 as an appealing carrier for amikacin targeted delivery.